1980
DOI: 10.1210/jcem-50-4-755
|View full text |Cite
|
Sign up to set email alerts
|

The Intraovarian Sites of Androgen and Estrogen Formation in Women with Normal and Hyperandrogenic Ovaries as Judged byin VitroExperiments*

Abstract: The status of oocytes, the follicular fluid concentrations of steroids, and the in vitro steroidogenic capacities of stromal tissue, thecal tissue, and granulosa cells from a 15-yr-old girl with primary amenorrhea, ovarian hyperandrogenism, insulin-resistant diabetes mellitus, and acanthosis nigricans were compared to those from normal adult human ovaries. Most oocytes (95%) in the antral follicles recovered from the hyperandrogenic ovaries were degenerative, and the antral fluid levels of testosterone were 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…In PCOS follicles, the low follicular fluid oestradiol concentrations were not different from size matched follicles in regularly cycling control women. These results are in agreement with previous studies that also found similar oestradiol concentrations (McNatty et al, 1980;Pache et al, 1992;Mason et al, 1994). Our findings are also in agreement with the only study to address the endogenous aromatase activity of granulosa cells in PCOS (Erickson et al, 1979).…”
Section: Discussionsupporting
confidence: 94%
“…In PCOS follicles, the low follicular fluid oestradiol concentrations were not different from size matched follicles in regularly cycling control women. These results are in agreement with previous studies that also found similar oestradiol concentrations (McNatty et al, 1980;Pache et al, 1992;Mason et al, 1994). Our findings are also in agreement with the only study to address the endogenous aromatase activity of granulosa cells in PCOS (Erickson et al, 1979).…”
Section: Discussionsupporting
confidence: 94%
“…Considering the fact that the action of high concentrations of insulin can be mediated via IGF-I receptors and that IGF-I receptor expression is increased in the thecal stromal cells of PCO ovaries despite the remarkable decrease in insulin receptors, it is possible that hyperinsulinemia in PCO patients may intensify androgen production by thecal stromal cells by reacting with IGF-I receptors. This possibility is further supported by the observation of McNatty et al [38] that ovarian stromal tissues of a patient with insulin-resistant diabetes produced 50-to 250-fold more androgen than did the ovarian stromal tissues from normal women. Taken together, as suggested by Barbieri et al [6,39], it is likely that one of the common disorders in PCO might be insulin resistance, with a consequent increase in insulin levels, which in turn stimulates ovarian thecal stromal androgen production.…”
Section: Discussionmentioning
confidence: 78%
“…Investigations in 1993 showed fasting blood sugar (FBS) level of 5.7 mmol/L, follicle stimulating hormone (FSH) 11 IU/L (normal [3][4][5][6][7][8][9][10][11][12], luteinizing hormone (LH) 11 IU/L (normal 0. [5][6][7][8][9][10][11], and prolactin (PRL) 415 mIU/L (normal 55-450).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11], and prolactin (PRL) 415 mIU/L (normal 55-450). Oral glucose tolerance test (OGTT) showed a diabetic curve, while growth hormone (GH) was normal throughout the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation